The Foraging Behaviour of Wandering Albatrosses - CINDY DOYLE (2024)
Wandering albatrosses (Diomedea exulans) are amongst the largest seabirds in the world. They have a circumpolar distribution and mainly feed on pelagic squid, which are highly mobile, possess well-developed senses and mostly dwell at great depths where they are considered inaccessible to wandering albatrosses. How these birds find and capture these elusive, deepsea squid has been extensively debated in the literature. This research aims to investigate the foraging behaviour of chick-brooding wandering albatrosses, with particular focus on the diel partitioning of foraging behaviours and to examine the extent of anecdotally reported ‘circling behaviour’, where they spin on the surface of the water, which may be linked to foraging. To do this, high-resolution (40 Hz) data was collected using tags recording tri-axial acceleration and magnetic field intensity sensors attached to 24 individual wandering albatrosses breeding on Marion Island between 2007 and 2018. Individual foraging trips were found to have lasted between one and seven days across all the birds. Sixty-two percent of this total duration consisted of flying and 38% consisted of sitting on the surface of the water. Of the flight time, 47% occurred during the day time and 53% during the night time while 54% of the total time sitting on the surface of the water occurred during the day time and 46% occurred at night.Over a 24-hour period, the birds took off from the water surface to engage in flight a mean of 8.4 times during daylight and 7.2 times at night, with no significant difference between day and night. This accords with conventional belief that these birds locate their sparsely-distributed prey by searching during their flights over large distances, pitching down on the water periodically to exploit surface-located food. Long periods on the water were evident, and circling behaviour at this time was observed seven times in four individuals (17%). The duration of these bouts ranged from 4-64 minutes (x=32, SD=24) with all birds commencing circling during periods believed to be darkness/semi darkness. I suggest that the circling creates bioluminescence that attracts squid. These findings contribute to future research by demonstrating a novel foraging strategy as a behavioural response to external environmental conditions. This knowledge is becoming increasingly important with the growing anthropogenic pressures, particularly in the Southern Ocean